1990
DOI: 10.2307/1368412
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Use of Nest Trees by Breeding Red-Headed and Red-Bellied Woodpeckers and European Starlings

Abstract: THE WILSON BULLETIN l VoZ. 103, No. 1. March 1991-. 1990. Simultaneous use of nest trees by breeding Red-headed and Red-bellied woodpeckers and European Starlings. Condor 92:252-253. JACKSON, J. A. 1977. A device for capturing tree cavity roosting birds. N. Am. Bird Bander 2:14-15.-. 1978. Competition for cavities and Red-cockaded Woodpecker management. Pp. 103-l 12 in Management techniques for preserving threatened species (S. A. Temple, ed.). Univ. Wisconsin Press, Madison, Wisconsin.-. 1987. The Red-cockade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 4 publications
0
53
1
5
Order By: Relevance
“…In a study of Red-headed Woodpecker cavity usurpation in southeastern Montana, Kronland (2007) described the incidence of interspecific cavity usurpation, estimating that over 20% of Red-headed Woodpecker nest cavities were secured by usurpation, but did not describe any incidence of conspecific cavity usurpation. Given their tenacity in usurping interspecific nest cavities (Schwab and Monnie 1959;Ingold 1989;Kronland 2007), it would not be surprising if Red-headed Woodpeckers usurp and depredate conspecific nests as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Red-headed Woodpecker cavity usurpation in southeastern Montana, Kronland (2007) described the incidence of interspecific cavity usurpation, estimating that over 20% of Red-headed Woodpecker nest cavities were secured by usurpation, but did not describe any incidence of conspecific cavity usurpation. Given their tenacity in usurping interspecific nest cavities (Schwab and Monnie 1959;Ingold 1989;Kronland 2007), it would not be surprising if Red-headed Woodpeckers usurp and depredate conspecific nests as well.…”
Section: Discussionmentioning
confidence: 99%
“…Redheaded Woodpeckers have been documented usurping cavities from Red-bellied Woodpeckers (Melanerpes carolinus) (Ingold 1989), Northern Flickers (Colaptes auratus) (Kronland 2007), Hairy Woodpeckers (Picoides villosus) (Kronland 2007), Downy Woodpeckers (Picoides pubescens) (Schwab and Monnie 1959), and Mountain Bluebirds (Sialia currucoides) (Kronland 2007). However, whether Red-headed Woodpeckers will usurp, or attempt to usurp, conspecific nest cavities has not been reported or evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Vierling (1998) observed 59 pairs of the Lewis's Woodpecker (Melanerpes lewis) at their nest-hollows and only one hollow was lost to Common Starlings. A series of studies (Ingold 1989(Ingold , 1994(Ingold , 1996(Ingold , 1998 showed that in urban and rural areas, the Common Starling competed successfully with native woodpeckers. In one case, competition with the Red-bellied Woodpecker (Melanerpes carolinus) was intense; 52% of hollows were lost, leading to a significant reduction in fecundity (Ingold 1989).…”
Section: Level and Strength Of Evidencementioning
confidence: 99%
“…A series of studies (Ingold 1989(Ingold , 1994(Ingold , 1996(Ingold , 1998 showed that in urban and rural areas, the Common Starling competed successfully with native woodpeckers. In one case, competition with the Red-bellied Woodpecker (Melanerpes carolinus) was intense; 52% of hollows were lost, leading to a significant reduction in fecundity (Ingold 1989). However, for this species and the Red-headed Woodpecker (Melanerpes erythrocephalus) and Northern Flicker (Colaptes auratus), re-nesting and moving into more heavily forested areas where the Common Starling was sparsely distributed were successful strategies to reduce competition with the Common Starling.…”
Section: Level and Strength Of Evidencementioning
confidence: 99%
“…In North America, where European Starlings are introduced, there are many examples of nest-site competition with native species (McGilvrey & Uhler 1971, Jackson & Tate 1974, in many cases leading to reductions in breeding densities of the local species. There are specific examples of competition with some species of native woodpecker (Ingold 1989, Kerpez & Smith 1990, Troetschler 1976. In North America, population impacts have been reported at the local scale but a recent analysis at the national scale failed to find any evidence of an impact of this competition at the population level for most of the 25 cavity-nesting species studied (Koenig 2003).…”
mentioning
confidence: 99%